Survey on mining signal temporal logic specifications - Bartocci, Ezio; Mateis, Cristinel; Nesterini, Eleonora; Nickovic, Dejan (Information and computation, 2022)
Formal specifications play an essential role in the life-cycle of modern systems, both at the time of their design and during their operation. Despite their importance, formal specifications are only partially (if at all) available. Specification mining is the process of learning likely system properties from the observation of its behavior and its interaction with the environment. Signal temporal logic (STL) is a popular formalism for expressing properties of cyber-physical systems (CPS). In the last decade, the introduction of first methods for mining STL specifications from time series generated by CPS led to a new vivid area of research. This survey paper overviews methods for mining STL specifications from CPS behaviors, sketches different approaches found in the literature and presents them in an intuitive and didactic manner. It aims at presenting the most influential techniques and covers most important aspects of specification mining: template-based vs. template-free, model-based vs. model-free, passive vs. active, and supervised vs. unsupervised learning.